The World Intellectual Property Organization and it’s cooperation program - Janulevičienė, Alma (Information & Media, 1995)
This article is designed to intellectual property protection. As in 1992 Lithuania joined the World Intellectual Property Organization the theme became especially important in our days. In this article there is described the WIPO history, aims, tasks and functions; number of conventions and treaties dealing with specific categories of intellectual property, describing "new" ones; the main WIPO activities and it’s relationship with Lithuania and cooperation with other ungovernment organizations.